Central nervous system infections in renal transplant recipients. Issue 4 (12th June 2020) - Basic‐Jukic, Nikolina; Juric, Ivana; Furic‐Cunko, Vesna; Kastelan, Zeljko
Abstract: Background: The aim of this study is to determine the incidence, etiology, clinical characteristics, and outcomes of renal transplant recipients diagnosed and treated for central nervous system (CNS) infection at our institution. Methods: We analyzed data from all renal transplant recipients between January 2007 and December 2019 that were diagnosed and treated for CNS infections at our institution. Results: Of 1374 patients who received renal allografts, 13 were diagnosed with CNS infections (9 males), with a mean age of 53.5 years. Patients were diagnosed with CNS infections between 2 months and 11 years after the transplantation. Causative agents included JC virus, Streptococcus pneumoniae, Cryptococcus neoformans, Herpes zoster virus, Mycobacterium tuberculosis, Listeria monocytogenes, and West Nile virus . One patient had concomitant Nocardia and Neisseria infection. Immunosuppression was reduced in all patients. The patient with JC encephalitis and the patient with concomitant Neisseria and Nocardia meningitis died. One patient was returned to dialysis. Other patients recovered with differing levels of neurologic sequelae. Conclusion: Central nervous system infections in renal transplant recipients are rare. However, they are associated with significant morbidity and mortality. A high level of awareness is needed: neurological symptoms may be nonspecific and caused by non‐infectious conditions related to the underlying disease, or side‐effects of immunosuppressive drugs.